Beneficial Effect of Cordyceps militaris on Exercise Performance via Promoting Cellular Energy Production - Eunhyun Choi; Junsang Oh; Gi-Ho Sung (Mycobiology, 2020)
Cordyceps militaris has been reported to the diverse pharmaceutical effects including cancer, inflammatory diseases, and bacteria or virus infection. However, the effect of C. militaris on exercise performance has not yet been elucidated. In this study, we investigated the beneficial effect of C. militaris on exercise performance. To evaluate exercise performance, we prepared C. militaris ethyl acetate extract (CMEE) and conducted grip strength tests every week after administration. Additionally, blood samples were collected at the end of the experiment for biochemical analysis. The administration of CMEE slightly increased grip strength, and this result was similar to the red ginseng treated group. According to the result of biochemical analysis, CMEE had an effect on the biomarkers related to ATP generation pathway but had little influence on the muscle fatigue related biomarkers. Therefore, C. militaris has the possibility of improving exercise performance, which could be associated with the increase in ATP production rather than the decrease in muscle fatigue during exercise.